Reposdn: um método de organização e coordenação de aplicações em repositório para redes definidas por software - PINHEIRO, Rômulo Silva (Universidade Federal do Pará, 2017)
The adoption of the paradigm of Software Defined Networks - SDN by academic institutions and large companies like Google, Cisco, HP, among others, is already a reality. This paradigm is considered a solution to the new model of Future Internet due to its technical and economic viability. The SDN paradigm enables new perspectives in terms of abstractions, control and development applications, free from the limitations of current technologies environments. However there is still lack in the way the management and control of several existing applications in the Internet occurs. The programmability is key to successful paradigm for Software Defined Networks as it allows the separation of the data with the control plane level. However, in the context of this paradigm, manage input and output controllers for many applications is a relatively unexplored issue, since the SDN applications, routing applications such as, for example, are not organized in a controlled environment. This thesis proposes a method of organization and coordination applications in repository for software defined networks, called RepoSDN, which specifies, models and automates the processes needed for applications reaching the administrator can manage this and their uses in the network, making it simple, safe and agile. The RepoSDN presents a structure where each SDN application is managed within the network to reach out to controllers. Additionally, it contains a central repository, where any user can send their applications to share with management Software Defined Network, which use specific applications for your need. A prototype of RepoSDN, which implements the functionality of the applications repository and components designed to help in the management of applications on a programmable network was developed. The method of organization and coordination of applications repository for SDN helps the administrator to handle each application. The proposal has been validated through the development of the repository of application, which consisted in doing load testing in developed component testing. The objective of the components is becoming simpler method that applications are entered in the various types of controllers of Software Defined Networking, resulting in the proof of feasibility, scalability and exibility of RepoSDN.